God made me this way: same-sex attraction through the lens of evolutionary creation in Christian theology - Key, Jack A. C. (Theology & sexuality, 2024)
In an examination of same-sex attraction through the lens of evolutionary creation and Aquinas’ secondary causality, this paper seeks to challenge the understanding of many Christians today that this trait is a negative result of ‘the fall’. By presenting a new approach called the Evolutionary Evaluation Model, a set of five questions guide this process of fairly evaluating traits in humans today which seem to contradict God’s design for humanity. Using this model to evaluate existing peer-reviewed scientific evidence alongside theological considerations, same-sex attraction appears to have been intentionally designed by God. Within a minority of humans, this trait produces the ability to build social bridges and ensures the survival of their families. Whilst same-sex attraction is not a result of ‘the fall’, such individuals need God’s support to overcome barriers that neutralize the benefits of the trait.